2018
DOI: 10.3390/su10124682
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Misconceptions to the Concept of Resilience in Environmental Education

Abstract: Environmental education is shaped in response to societal and environmental realities and it reflects new interests and demands that enable sustainable transformations. In recent years, the concept of resilience has taken an increasingly significant role among practitioners, researchers, policymakers, and especially within the Sustainable Development Goals (SDGs). Despite its growing importance, the literature surrounding the concept of resilience has struggled to find a consensus on definitions and measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…Resilience is a wide concept that in general can be understood as the capacity of adaptation and transformation to external changes. Resilience is not necessarily a positive term, and it is often misconceived in the field of education, through an incomplete understanding of its adaptive nature and through not considering resilience for whom or to whom [12]. It is therefore very important to make a clear definition of what we understand and the limits of the concept in the context of this paper.…”
Section: Towards Socioecological Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Resilience is a wide concept that in general can be understood as the capacity of adaptation and transformation to external changes. Resilience is not necessarily a positive term, and it is often misconceived in the field of education, through an incomplete understanding of its adaptive nature and through not considering resilience for whom or to whom [12]. It is therefore very important to make a clear definition of what we understand and the limits of the concept in the context of this paper.…”
Section: Towards Socioecological Resiliencementioning
confidence: 99%
“…Recent research explores the way in which environmental education relates to personal and systems resilience [12,13]. Chawla et al [14] found that contact with nature in school allows kids to find peace and to build social competencies and cooperative social relationships.…”
Section: Towards Socioecological Resiliencementioning
confidence: 99%
“…In general, resilience is recognized as the ability to prepare for and adapt to changing conditions to withstand and recover rapidly from disruptions due to deliberate attacks, accidents or naturally threats [16]. Resilience aspects are also studied together with other practical implications, such as food system resilience [17], [18], [19], urban design for resilient cities [20] and communities [21], resilience within the environmental education practice [22], resilient libraries as part of larger, complex systems [23], or, more comprehensive, resilience of systems [24], [25], [26], enterprises [27], and resilience for managerial implications [28].…”
Section: Introductionmentioning
confidence: 99%
“…At a global scale, the SDGs have emerged as a political framework to guide, align, and resolve, though partially, these cities' development issues. Therefore, it is necessary that "every global citizen should be able to acquire relevant knowledge, skills, and values to advance humanity's collective progress towards sustainable futures" [22].…”
Section: Introductionmentioning
confidence: 99%
“…Es importante profundizar en el vínculo que existe entre Desarrollo Social Sostenible y la Educación Ambiental (Kharrazi, Kudo & Allasiw, 2018;Büssing, Schleper & Menzel, 2018), pues de esta manera se podrán consolidar las estrategias para poder abordar los problemas socioecológicos contemporáneos (Yun-Ciao & Shang-Chia, 2018); pues la educación resulta un valor de uso estratégico para implementar procesos de enseñanzaaprendizaje de los ciudadanos (Martínez-Borreguero, Maestre-Jiménez, Mateos-Núñez & Naranjo-Correa, 2019). Por tales motivos es que Ecocience International Journal publica el presente número especial que toma la forma de un Dossier en cuyas páginas escriben diversos académicos e investigadores de reconocido prestigio dedicados al estudio crítico e interdisciplinario sobre la Educación como un factor determinante para la Sostenibilidad.…”
Section: Introductionunclassified